Shifts in Fungal Communities and Potential Functions Under Masson Pine Forest-to-Tea Plantation Conversion in Subtropical China - Xiaofang Ma; Xiaofang Ou; Dan Chen; Yong Li; Cameron McMillan; Tida Ge; Ji Liu; Min Xue; Cong Wang; Weijun Shen (Microorganisms)
The land-use conversion of Masson pine forests to tea fields is extensively practiced across subtropical China, primarily driven by its economic benefit. However, the effects of this conversion on soil fungal communities and functional guilds are poorly understood. Herein, a field experiment was conducted in a Masson pine forest (F), a 5-year-old tea plantation without (FT-CK) fertilization or with (FT-N), and a 30-year-old tea plantation (FT-O) to assess the impact of Masson pine forest-to-tea conversion on soil fungal abundance, community structure, and functional guilds by using qPCR and high-throughput sequencing. Compared to F, fungal abundance significantly decreased by 95%, 68%, and 79% in FT-CK, FT-N, and FT-O, respectively, probably caused by the decreased total nitrogen content and habitat disruption. Fungal alpha diversity significantly increased in FT-N and FT-O compared to FT-CK. FT-O presented the highest percentages of Mortierella among treatments, which favours soil organic carbon accumulation. FUNGuild-based predictions showed that FT-CK and FT-N had higher relative abundances of plant pathogens than F and FT-O. FT-O presented the highest percentages of litter and soil saprotrophs but exhibited the lowest percentages of ectomycorrhizal fungi among treatments, likely driven by increased soil organic carbon, total nitrogen, and total phosphorus content. Our findings demonstrate that Masson pine forest-to-tea conversion significantly degrades soil fungal community and function, highlighting the urgent need for soil management strategies (e.g., organic amendments) to enhance soil health in tea agroecosystems.